Cross‐border dimensions of Arctic climate change impacts and implications for Europe - Mosoni, Claire; Hildén, Mikael; Fronzek, Stefan; Reyer, Christopher P. O.; Carter, Timothy R. (2025)
The Arctic has warmed almost four times faster than the rest of the globe during the past four decades. This has led to multiple impacts in the Arctic such as the melting of glaciers and the Greenland ice sheet, sea ice retreat, permafrost thaw, altered species distribution and abundance, changes in hydrology and snow conditions, and altered wildfire regimes. These documented and projected impacts in the region can also propagate across borders, creating risks and opportunities requiring adaptation responses well beyond the Arctic. By undertaking a systematic literature review that uses a conceptual framework for cross-border climate change impacts, we demonstrate how local impacts of the type described above, which are often analyzed separately in the literature, may initiate knock-on effects that can be transmitted and transformed across borders. We illustrate examples of six categories of cross-border risks resulting from this impact transmission and potentially requiring adaptation. These concern biophysical impacts, trade, infrastructure, finance, geopolitical relationships and human security and social justice. We examine potential adaptation options for responding to such cross-border risks that are of relevance for Europe. The systemic approach taken in this paper promotes improved understanding of trade-offs between potential benefits and risks, assists priority-setting for targeting adaptation interventions, and can account for the important role of non-climatic drivers in amplifying or dampening the cross-border risks of climate change impacts in the Arctic.